Language of Gestures: Mudrā, Mirror, and Meaning in Śākta Philosophy - Sthaneshwar Timalsina (Religions, 2021)
By contextualizing the ways gestures are used and interpreted in tantric practice and philosophy, this paper explores the cultural and cognitive domains of corporeal expression. Initiating the conversation with descriptions of basic dance gestures and widely understood emotional expressions, the paper proceeds to address the generative nature of corporeal language as it contextualizes varied forms of esoteric experience. Confronting simplistic readings of gestural language, the core argument here is that tantric gestures introduce a distinctive form of embodied language that relies on a propositional attitude for deciphering their meanings. This process becomes a ritual in its own right. Even when we accept that gestures represent meaning, tantric gestures are understood to mirror the innate experience, prior to being shaped by language and culture, and in this sense they reflect the absolute. As a consequence, language becomes physical in time and space, and even when language transcends itself, it remains embodied. In sum, tantric gestures can be deciphered to unravel the deeper layers inherent to the sign system, and this is possible only when we are open to critically engaging folk theories.